Teaching to Teach, a Unique Approach from the Disciplines of Musical Creation - Guzmán Barrios, Rafael (Journal of the University of Zulia, 2024)
The present article addresses the importance of training future music educators (creative area) with pedagogical competencies, not just technical ones. It identifies the necessary resources and tools for teaching musical composition, emphasizing the need for a metacognitive approach. The methodology includes documentary research and participant observation, highlighting the teacher-student relationship and its impact on the creative process. The results underscore the need to change the perception of music pedagogy as a secondary option, promoting comprehensive training that covers technical, theoretical, and pedagogical aspects. The study concludes that teacher preparation must adapt to diverse educational needs, integrating digital competencies and innovative methodologies.